Pendampingan Rutinan Yasin Dan Tahlil Jama’ah Putra Sebagai Upaya Pembentukan Karakter Religius di Desa Sidowarek Kecamatan Ngoro - M Dzikrul Hakim Al Ghozali; Didin Sirojudin (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Yasin and Tahlil male are routine religious organizations that should be carried out by residents of Sidowarek Village, Ngoro District, Jombang Regency once a week. The congregation's participants consisted of three hamlets, namely Kepuh Pandak Hametown, Genjong Lor Hametown and Wonorejo Hametown, where the majority of the congregation were less enthusiastic about this religious activity. This greatly affects the daily routine of the community in socializing. Therefore, researchers think it is necessary to provide assistance to these activities to make them more meaningful. This service research uses a participatory method. In this case, the researcher collaborates with the Yasin and Tahlil Putra activity managers to design activities that are considered capable of shaping the religious character of the community by designing the content of activities with a series of focused events aimed at increasing religious awareness and insight. The results of this service research are that after conducting interviews with several sources, the data on the percentage of the congregation's understanding is obtained that understands 60% = 73 people, understands 30% = 36 people, does not understand 10% = 12 people. This shows that the people of Sidowarek Village are more enthusiastic than before.